Use of Platelet Rich Plasma in the Treatment of Diabetic Foot. Case Report - Enrique Ramón Rodríguez Reyes; Alberto Sánchez Garrido; Elsy Labrada González (Revista Finlay)
Diabetic foot is one of the most serious complications of diabetes mellitus. An alternative for its treatment is the use of platelet-rich plasma due to its ability to stimulate angiogenesis, cell proliferation and collagen synthesis. The case of a 60-year-old female patient with a medical history of type 2 diabetes mellitus diagnosed 15 years ago, who suffered a puncture wound in the region of the sole of the foot, is presented. After a year of treatment without improvement in the ulcer, it was decided to apply platelet-rich plasma therapy and healing was achieved in a period of approximately 8 weeks. Platelet-rich plasma represents an emerging and promising therapy for the treatment of diabetic foot. The clinical case presented shows the positive results in the healing of ulcers and improves the quality of life of patients with the use of this procedure.